Hypoglycemic Effect of Vitexin in C57BL/6J Mice and HepG2 Models - Weidong Xu; Jiayao Li; Weipeng Qi; Ye Peng (Journal of Food Quality)
Apigenin-8-C-glucoside (vitexin), a natural phytochemical contained in hawthorn, has been reported to have versatile beneficial bioactivities, such as antioxidation, anticancer property, and adipogenesis inhibition. The present research aimed to determine the influence of vitexin on insulin resistance elicited by HFD in mice and HepG2 cells. Vitexin markedly alleviated body weight gain and improved glucose and insulin intolerance induced by HFD. Vitexin partially normalized blood glucose, cholesterol, TNF-α, and hepatic lipid content. Moreover, vitexin recovered the reduced glucose uptake induced by glucosamine. The present results indicate that vitexin prevents HFD-induced insulin resistance.